Proces budowy porozumienia i współpracy między społecznościami regionu lubuskiego i państw Unii Europejskiej w latach 1993-1994 na łamach "Codziennego Expressu Zachodniego" = The process of building understanding and cooperation between the communities of the Lubusz region and European Union countries in 1993-1994, in "Codzienny Expres Zachodni" ("The Daily Western Expres") - Dzieżyc, Longin (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This study shows the process of understanding and cooperation that has been going on, involving communities of the Lubusz region and the European Union. Its determining conditions have been changes in the subjectivity of the civic body, responsible for shaping an attitude of conscious openness and engagement on the part of local communities. Regional daily newspapers have played a significant role in bringing about and promoting changes, by presenting the emerging signs of cooperation, starting from the construction of various kinds of social interaction through administrative and economic cross-border co-operation and extensive cultural exchange. The issue is presented using selected articles and press reports published in "Codzienny Express Zachodni" ("The Daily Express West") from August 1993 to the end of July 1994. The particular frame of reference of thearticle, together with its broad substantive scope, mean that it is not possible to comprehensively cover all issues relevant to giving an account of this process.
Keywords: Ziemia Lubuska; Unia Europejska; prasa; prasa codzienna; współpraca; Codziennny Expres Zachodni (czasopismo); Lubusz Land; European Union; press; daily press; cooperation